Vasorelaxant And Antihypertensive Effects Of 3,4,7,2',4'-Pentahydroxyflavone In In Vitro And In Vivo Models - Wan Yin, Tew (2024)
Hypertension is one of the chronic medical conditions characterised by consistently high blood pressure exerted against the wall of blood vessels. It has emerged as a major global health concern due to its increasing worldwide prevalence. Although numerous antihypertensive medications are available in the market, many are reported to have low efficacy and frequently come with adverse effects or contraindications. Consequently, the current study was designed to identify a potential antihypertensive agent which could avoid all the issues associated with currently market available medications. Morin, a flavonol which was known for its diverse pharmaceutical properties, was selected to evaluate its vasodilatory and antihypertensive activities using in vitro and in vivo approaches, respectively. The vasodilatory effect of morin and its underlying mechanism were evaluated in vitro using aortic rings assay. The results revealed that morin exerts its vasodilatory effects through multiple mechanisms pathways, including endothelium-dependent and endothelium-independent pathways.